Use of alternative communication with pictures for outpatient periodontal treatment in fragile X syndrome patients - Rafael Ferreira; Adriana Gledys Zink; Paulo Sérgio da Silva Santos (Wolters Kluwer Medknow Publications, 2021)
The purpose of this article is to discuss the clinical management and behavior during periodontal treatment in two patients with fragile X syndrome (FXS) using alternative communication with pictures (ACP). Both patients had a history of previous dental care only possible under general anesthesia. The ACP was used to anticipate the activities to be carried out, promoting ambiance, improving the professional-patient communication, and decreasing the stress of the patient. It was possible to carry out outpatient care without oral sedation and containment/physical restraint in both patients, being surpassed the communicative and behavioral difficulties. These case reports allow us to re-think dental care under general anesthesia or other invasive methods for patients with FXS. Therefore, the ACP is an important mediator tool that can facilitate the insertion and the management of patients with FXS, allowing the dental care outpatient clinic to promote oral health and quality of life for these patients, improving adherence to periodontal treatment and the periodontal maintenance for oral hygiene.